RAPID EX SITU COLLECTION AND THERMAL BEHAVIOR ANALYSIS OF VOLATILE ORGANIC MATTERS BY THERMAL EXTRACTION CONE CHAMBER FOR HIGH UN-BURNT CARBON COAL FLY ASH - Anggoro Tri Mursito (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2005)
A thermal extraction cone chamber system has been modified to measure differential thermal functions and products where overall volatile organic matters are lost to the environment during heating. The aims of the research are to analyze and measure the thermal behavior of high un-burnt carbon coal fly ash derived from textile industrial power in Bandung. Efforts are being made to find the solution in large-scale utilization for alternative energy based on their by product. The sample analysis show that volatile organics matter exceed 30%, which means that others oxides element content are independently favorable. The modified cone chamber can collect the sample up to the total volumes of 30% of the chamber. In contrast to traditional chamber sample collectors, the modified cone extracts volatile organics matter from high un-burnt carbon coal ash divided in two treatments. Results show that the energy of pyrolisis, direct combustion or simple carbonization can be recovered (20%-42%) from wet or dry sample, with extraction efficiency compound-specific. During the direct combustion experimentation, resulted to the embedded energy is pushing up to 2790C for the average of volatile organic matters of 34% and for pyrolisis experimentation is 3300C for average volatile organic matters of 30%. The maximum thermal productivity values of 80 minutes for the direct combustion is 10220C and for pyrolisis is 10310C, and the contrary of 10 minutes, for the direct combustion is 7430C and for pyrolisis is 7010C